Information Technology Analysis Using COBIT 5 Domain DSS in Sub. Bagian Infrastruktur Pertanahan ATR/BPN Kota Bengkulu - Arie Vatresia; Ferzha Putra Utama; Sandhy Akmal Nasution (Soegijapranata Catholic University, 2022)
ATR/BPN Kota Bengkulu uses information technology to manage land records, draw plots of land, and to document activities carried out in each area for reporting. In the use of IT, it has not implemented Best Practice and has never been evaluated so that it does not yet know the level of maturity. The purpose of this study is to provide recommendations to the ATR/BPN Kota Bengkulu to report to the center. The framework used in IT analysis is COBIT 5 with a focus on Domain DSS (Delivery, Service and Support). The result of this research is to map the strategic plan of ATR/BPN Kota Bengkulu with IT-Related Goals COBIT 5 with BSC (Balanced Score Card) dimension which gets the domains DSS01, DSS02, DSS03, DSS04, DSS05, and DSS06. And the results of each DSS domain used are DSS01 Manage Operations with a value of 3.75, DSS02 Manage Service Requests and Incidents with a value of 3.63, DSS03 Manage Problems with a value of 3.5, DSS04 Manage Continuity with a value of 3.70, DSS05 Manage Security Services with a value of 3.64 and DSS06 Manage Business Process Control with a value of 3.92. With these results the DSS domain gets a value 3. So that the rounding is done including into Level 4 Predictable Process and recommendations are given to achieve the next criteria, namely Level 5 Optimizing Process.